Partnerships with the Private Sector - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2017)
The International Center for Tropical Agriculture (CIAT), a member of the CGIAR Consortium, develops technologies, tools and new knowledge that better enable farmers, especially smallholders, to make agriculture eco-efficient— that is, competitive and profitable as well as sustainable and resilient. With headquarters near Cali, Colombia, CIAT conducts research for development in tropical regions of Latin America, Africa, and Asia. Dynamic partnerships are critical to enabling the public sector to translate research into tangible, on-the-ground impact, while also allowing the private sector to achieve its economic goals. CIAT appreciates the important contributions that its private sector partners are making to reach more farmers and consumers faster.